Development of electropulsation for the extraction of protein from underutilized agro-source pinto bean, as an alternative solution to the issue of protein malnutrition. - Gan, Chee Yuen (Universiti Sains Malaysia, 2015)

(untitled)
Pinto bean showed its potential as an alternative source of protein. High amount of protein was successfully extracted from pinto bean. An optimum condition for the extraction was obtained. Therefore, this protein source could be used to overcome protein-malnutrition issue.